2021
DOI: 10.3390/cancers13235940
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Tanning and the Risk of Overall and Early-Onset Melanoma and Non-Melanoma Skin Cancer: Systematic Review and Meta-Analysis

Abstract: The aim of this study was to examine the association between indoor tanning use and the risk of overall and early-onset (age < 50) melanoma and non-melanoma skin cancer (NMSC). To evaluate the association between indoor tanning and skin cancer, a systematic review of the literature published until July 2021 was performed using PubMed, EMBASE, and MEDLINE. Summary relative risk (RR) from 18 studies with 10,406 NMSC cases and 36 studies with 14,583 melanoma cases showed significant association between skin ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Several systematic reviews and meta-analyses have consistently established a statistically significant higher risk of cutaneous melanoma with the use of sunbeds (summarized in Table 2 ) [ 18 , 37 , 38 , 39 , 40 , 41 , 42 ]. Nevertheless, the quantification of the measure of the association of sunbed use with melanoma risk is hindered by limitations inherent to the design of individual studies.…”
Section: Sunbed Use and Risk Of Cutaneous Melanomamentioning
confidence: 99%
See 4 more Smart Citations
“…Several systematic reviews and meta-analyses have consistently established a statistically significant higher risk of cutaneous melanoma with the use of sunbeds (summarized in Table 2 ) [ 18 , 37 , 38 , 39 , 40 , 41 , 42 ]. Nevertheless, the quantification of the measure of the association of sunbed use with melanoma risk is hindered by limitations inherent to the design of individual studies.…”
Section: Sunbed Use and Risk Of Cutaneous Melanomamentioning
confidence: 99%
“…Nevertheless, the quantification of the measure of the association of sunbed use with melanoma risk is hindered by limitations inherent to the design of individual studies. The most recent meta-analysis of An et al (2021), included 36 studies in 14,583 melanoma cases and reported that the risk of cutaneous melanoma increased by 27% for those ever exposed to indoor tanning (RR: 1.27, 95% CI: 1.16–1.39) [ 37 ]. Similar risk estimates have been reported in previous meta-analyses (RR ranging from 1.15 to 1.27) ( Table 2 ).…”
Section: Sunbed Use and Risk Of Cutaneous Melanomamentioning
confidence: 99%
See 3 more Smart Citations